Neoproterozoic bimodal magmatism in the Cathaysia Block of South China and its tectonic significance - Li, W.; Li, X.; Li, Zheng-Xiang (Elsevier Science BV, 2005)
SHRIMP U–Pb zircon age, geochemical and Sm–Nd isotopic results are reported for the Mamianshan volcanic rocks in the Cathaysia Block of southeastern South China. The Mamianshan volcanic rocks are bimodal in composition and are dominantly transitional to mildly alkaline basalts and subordinate alkaline rhyolite, with an eruption age of 818±9 Ma. The basaltic samples are characterized by LREE-enriched and “humped” trace element patterns, similar to many alkali basalts in continental rifts. Variable _Nd(T) values between +3.33 and-4.35 indicate that the primary magma of these basalts was derived from an OIB-like mantle source and underwent fractional crystallization plus crustal contamination. The rhyolitic rocks are highly enriched in Th, Ta, Nb, REE, Zr, Hf and Y and depleted in Sr, P, Eu and Ti, sharing affinity to A1-type granites. Combined with their slightly positive _Nd(T) values (+0.22 to +0.92), the Mamianshan felsic rocks were most likely generated by partial melting of the regional Paleoproterozoic Mayuan amphibolites. The Mamianshan bimodal volcanic rocks in the Cathaysia Block are coeval with the widespread intraplate magmatism around the Yangtze Block. Our results support the idea that a coherent South China Craton was formed during the ca. 1.0 Ga Sibao orogeny, and it subsequently underwent extensive continental rifting related to mantle plume or superplume activities beneath Rodinia since ca. 825 Ma.